Familial Infantile Myoclonic Epilepsy : Clinical Features in a Large Kindred with Autosomal Recessive Inheritance - De Falco, Fabrizio A.; Majello, Luigi; Santangelo, Roberto; Stabile, Mariano; Bricarelli, Franca Dagna; Zara, Federico (Epilepsia (Copenhagen), 2001)
Purpose: To describe the clinical features of a large kindred with familial infantile myoclonic epilepsy (FIME) with autosomal recessive inheritance, and to discuss the nosology of the early infantile myoclonic epilepsies (IMEs). Methods: The family descends from the intermarriage of two couples of siblings. In a previous study, we mapped the genetic locus to chromosome 16p13.We analyzed results of family records and personal history, psychomotor development, neurologic examination, epilepsy features, and EEG recordings for each subject. Results: FIME has a strong penetrance (eight affected of 14 subjects) and a homogeneous clinical picture. Like the benign form of infantile myoclonic epilepsy (BIME), FIME is a true idiopathic IME with unremarkable history, no neurologic or mental impairment, good response to treatment, and normal interictal EEG pattern. Conversely, onset with generalized epileptic seizures without fever (four patients) or with fever (one patient), frequency and duration of the myoclonic seizures, occurrence of generalized tonic–clonic seizures (GTCSs) in all patients and persistence of seizures into adulthood are characteristics of the severe infantile myoclonic epilepsy (SIME). Conclusions: Clinical overlap probably exists among the myoclonic epilepsies of infancy. FIME differs from other forms of IME in its phenotypic features. The peculiar mode of inheritance is explained by the genetic background of the family. Genetic studies suggest linkage to chromosome 16 in familial cases of true IME.